MATHEMATICAL MODEL OF INTEGRAL CRITERION OF COMPETITION POTENTIAL OF MARITIME-RIVER HIGHER EDUCATIONAL ESTABLISHMENT. ﻿ (Journal of Information Technologies in Education (ITE), 2012)
The competitive potential (CP) of maritime-river higher educational establishment in the conditions of a modern market of educational service is analyzed. The model of strategic resources (SR) is formalized.The mathematical model of an integral criterion of the competitive potential of higher educational establishment on the basis of Guermeyer’s method is built.It is proved that the discreteness of competitive edges is a reason of the formation of fuzzy resources and requires the construction of the functions belonging to competition potential of higher educational establishment.
Keywords: competitive edges (kp); competitive potential (КР); discreteness; functions of belonging; fuzzy resources; strategic resources (SR)